Patients' Perceptions of an Exercise Program Delivered Following Discharge From Hospital After Critical Illness (the Revive Trial). (November 2019) - Ferguson, Kathryn; Bradley, Judy M.; McAuley, Daniel F.; Blackwood, Bronagh; O'Neill, Brenda
Background: The REVIVE randomized controlled trial (RCT) investigated the effectiveness of an individually tailored (personalized) exercise program for patients discharged from hospital after critical illness. By including qualitative methods, we aimed to explore patients' perceptions of engaging in the exercise program. Methods: Patients were recruited from general intensive care units in 6 hospitals in Northern Ireland. Patients allocated to the exercise intervention group were invited to participate in this qualitative study. Independent semistructured interviews were conducted at 6 months after randomization. Interviews were audio-recorded, transcribed, and content analysis used to explore themes arising from the data. Results: Of 30 patients allocated to the exercise group, 21 completed the interviews. Patients provided insight into the physical and mental sequelae they experienced following critical illness. There was a strong sense of patients' need for the exercise program and its importance for their recovery following discharge home. Key facilitators of the intervention included supervision, tailoring of the exercises to personal needs, and the exercise manual. Barriers included poor mental health, existing physical limitations, and lack of motivation. Patients' views of outcome measures in the REVIVE RCT varied. Many patients were unsure about what would be the best way of measuring how the program affected their health. Conclusions: This qualitative study adds an important perspective on patients' attitude to an exercise intervention following recovery from critical illness, and provides insight into the potential facilitators and barriers to delivery of the program and how programs should be evolved for future trials.